2017
DOI: 10.1016/j.surfcoat.2017.09.066
|View full text |Cite
|
Sign up to set email alerts
|

Fracture behavior and thermal durability of lanthanum zirconate-based thermal barrier coatings with buffer layer in thermally graded mechanical fatigue environments

Abstract: The effects of buffer layer on the fracture behavior and lifetime performance of lanthanum zirconate (La 2 Zr 2 O 7 ; LZO)-based thermal barrier coatings (TBCs) were investigated through thermally graded mechanical fatigue (TGMF) tests, which are designed to simulate the operating conditions of rotating parts in gas turbines. To improve the thermal durability of LZO-based TBCs, composite coats consisting of two feedstock powders of LZO and 8 wt.% yttria-doped stabilized zirconia (8YSZ) were prepared by mixing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In another word, the appearance of narrow cracks is beneficial to prevent the vertical cracks propagating during the process of stress relief. In our previous study [28], the blended LZO-YSZ based TBCs with RP-YSZ buffer layer generated more vertical cracks than YGYZ-based TBCs. Therefore, the YGYZ-based TBCs showed a better thermal durability in the low-frequency cycling TGMF test.…”
Section: Accepted Manuscriptmentioning
confidence: 85%
“…In another word, the appearance of narrow cracks is beneficial to prevent the vertical cracks propagating during the process of stress relief. In our previous study [28], the blended LZO-YSZ based TBCs with RP-YSZ buffer layer generated more vertical cracks than YGYZ-based TBCs. Therefore, the YGYZ-based TBCs showed a better thermal durability in the low-frequency cycling TGMF test.…”
Section: Accepted Manuscriptmentioning
confidence: 85%
“…However, due to its low coefficient of thermal expansion, high thermal stresses occur near the interface between the top and bond coats, causing delamination and low durability in cyclic thermal environments. Vassen [4,[9][10][11] and our group [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] have developed layered LZ based coatings to mitigate the issue. Double-ceramic-layer (DCL) TBCs have been proposed, which include a top ceramic layer and a thin ceramic buffer layer.…”
Section: Development Of Advanced Tbc Materials For Advanced Gas Turbimentioning
confidence: 99%
“…Sivakumar et al reported that the adhesive strengths were 6.63 MPa, 6.17 MPa, and 3.73 MPa, which corresponded to the plasma sprayed La2Zr2O7 coatings with the porosity of 16%, 21% and 28%, respectively [11]. Lyu et al investigated the cycling performance of La2Zr2O7/8YSZ composite coating in TGMF tests, and indicated that La2Zr2O7/8YSZ buffer layer improved the TGMF cycling performance [12]. A few recent reviews of La2Zr2O7 based coating materials were given by Bakan [13] and Zhang [14].…”
Section: Introductionmentioning
confidence: 99%